Report on the Conference on Transposition and Genome Engineering 2015 (TGE 2015): advancing cutting‐edge genomics technology in the ancient city of Nara. (29th March 2016) - Woltjen, Knut; Yamamoto, Takashi; Kokubu, Chikara; Takeda, Junji
Abstract : From November 17 to 20 in 2015, the Conference on Transposition and Genome Engineering 2015 (TGE 2015) was held at Nara Kasugano International Forum—IRAKA—in Nara, Japan, located at the center of Nara Park. All of the presentations were carried out at Nohgaku hall in Nara Kasugano International Forum—IRAKA. Participation totaled 148 persons (30 international, 118 domestic), who were able to engage in lively scientific discussions over the 4‐day period. The guest speaker list consisted of many top‐notch international researchers, an achievement for which the conference received praise from the attendees. There were 36 oral presentations including the keynote lecture (22 presentations from guest speakers, complemented with 14 selected from abstract submissions). Additionally, there were 46 poster presentations. The conference uniquely combined research mainly from two different genomics approaches: (i) transposon technology allowing random genomic integration followed by gene discovery‐related phenotypes and (ii) genome editing technology with designer nuclease allowing precise modification of a gene‐of‐interest. Abstract : Group photograph from the Conference on Transposition and Genome Engineering 2015 (TGE 2015) held at Nara Kasugano International Forum—IRAKA—in Nara, Japan on 17 to 20 November 2015.